Faktor-Faktor yang Berhubungan dengan Mortalitas pada Pasien Pediatrik yang Menjalani Pembiusan di Masa Pandemi Covid-19 di RSUP DR Sardjito - Djajantisari; Getar M, Geza Getar M; Widyastuti, Yunita (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2023)
Background: Anesthesia has the potential to cause physiological changes that lead to morbidity and mortality. Perioperative mortality alone is higher in children than in adults. During this time, the COVID-19 pandemic has affected anesthesia care around the world. The practice of pediatric surgery shows a significant decrease in the frequency of elective surgeries during the pandemic compared to the last three months before the pandemic. Surgical delays that occur, especially in